Consent for Anesthesia Clinical Trials on the Day of Surgery: Patient Attitudes and Perceptions - Murphy, Glenn S.; Szokol, Joseph W.; Avram, Michael J.; Greenberg, Steven B.; Shear, Torin D.; Vender, Jeffery S.; Landry, Elizabeth (Anesthesiology (Philadelphia), 2016)
BACKGROUND:Opportunities for anesthesia research investigators to obtain consent for clinical trials are often restricted to the day of surgery, which may limit the ability of subjects to freely decide about research participation. The aim of this study was to determine whether subjects providing same-day informed consent for anesthesia research are comfortable doing so. METHODS:A 25-question survey was distributed to 200 subjects providing informed consent for one of two low-risk clinical trials. While consent on the day of surgery was permitted for both studies, a preadmission telephone call was required for one. The questionnaire was provided to each subject at the time of discharge from the hospital. The questions were structured to assess six domains relating to the consent process, and each question was graded on a 5-point Likert scale (1 = strongly disagree to 5 = strongly agree). Overall satisfaction with same-day consent was assessed using an 11-point scale with 0 = extremely dissatisfied and 10 = extremely satisfied. RESULTS:Completed questionnaires were received from 129 subjects. Median scores for satisfaction with the consent process were 9.5 to 10. Most respondents reported that the protocol was well explained and comprehended and that the setting in which consent was obtained was appropriate (median score of 5). Most patients strongly disagreed that they were anxious at the time of consent, felt obligated to participate, or had regrets about participation (median score of 1). Ten percent or less of subjects reported negative responses to any of the questions, and no differences were observed between the study groups. CONCLUSION:More than 96% of subjects who provided same-day informed consent for low-risk research were satisfied with the consent process.